Cross-cultural assessment of knowledge and attitudes toward Folic acid: Instrument development and validation in Thailand and Yemen - Rana Ali Al-Qaari; Saranthorn Khuankaew; Mahittha Suttiserm; Siraphat Pornsuksawang; Pawat Boonnop; Somchai Manopatanakul; Siribang-on Piboonniyom Khovidhunkit; Sasipa Thiradilok; Chanita Tantipoj (PLoS ONE, 2026)
Folic acid is essential for the prevention of neural tube defects and other congenital anomalies, yet awareness and uptake vary across cultural and resource settings. Reliable tools to assess women’s knowledge and attitudes toward Folic acid are limited, particularly in cross-cultural contexts. This study aimed to develop and validate a culturally adaptable questionnaire in two distinct populations: Thailand and Yemen. In this cross-sectional instrument development and validation study, the questionnaire was developed through literature review and expert consultation, and comprised demographics, eight knowledge items, and ten attitude items. Following content validation, pilot testing, and test–retest reliability assessment, exploratory and confirmatory factor analyses were performed. Cronbach’s alpha was calculated for internal consistency. Data were collected from 538 women of reproductive age (Thai: 104; Yemeni: 434) via an online self-administered survey. The attitude scale demonstrated strong psychometric properties, with high internal consistency (α = 0.88 in both groups), coherent factor structures, and excellent model fit in the Yemeni sample (RMSEA = 0.054, CFI = 0.973, TLI = 0.965). Knowledge scores varied across items, with higher awareness in dietary source and timing-related items, and lower scores in statistical and biological knowledge. The Yemeni version showed lower internal consistency in the knowledge section (α = 0.59), reflecting content heterogeneity. Despite contextual differences, the instrument demonstrated psychometric coherence in both groups, though model fit was more robust in the Yemeni sample. In conclusion, this study developed and validated a brief questionnaire to assess knowledge and attitudes toward Folic acid in culturally diverse settings. The tool showed good psychometric performance and is suitable for use in research and public health interventions, particularly in low-resource or cross-cultural environments.